2019
DOI: 10.1016/j.ica.2018.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and cytotoxicity assays of a copper(II) nitrate complex with a tridentate ONO acylhydrazone ligand. Spectroscopic and theoretical studies of the complex and its ligand

Abstract: Synthesis, crystal structure and cytotoxicity assays of a copper(II) nitrate complex with a tridentate ONO acylhydrazone ligand. Spectroscopic and theoretical studies of the complex and its ligand, Inorganica Chimica Acta (2018), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…Scientific reports showed that copper complexes with IC 50 values in the low micromolar range (<10 µM) have been recognized as potent cytotoxic agents against different human cancer cell lines [8]. In this sense, previous results of our group on a copper(II) complex with a tridentate ONO acylhydrazone ligand with benzene rings [50], showed higher IC 50 values than CuHL for MG-63 (8.8 ± 0.3 µM) and A549 (12 ± 1.2 µM), hence suggesting that the thiophene ring may play some role in the anti-cancer activity of the metal complex. Besides, the biological effects of four Cu(II) complexes with Schiff base ligands on human colon carcinoma cells (HT-29) have been also investigated.…”
Section: Cell Viability Studymentioning
confidence: 56%
See 1 more Smart Citation
“…Scientific reports showed that copper complexes with IC 50 values in the low micromolar range (<10 µM) have been recognized as potent cytotoxic agents against different human cancer cell lines [8]. In this sense, previous results of our group on a copper(II) complex with a tridentate ONO acylhydrazone ligand with benzene rings [50], showed higher IC 50 values than CuHL for MG-63 (8.8 ± 0.3 µM) and A549 (12 ± 1.2 µM), hence suggesting that the thiophene ring may play some role in the anti-cancer activity of the metal complex. Besides, the biological effects of four Cu(II) complexes with Schiff base ligands on human colon carcinoma cells (HT-29) have been also investigated.…”
Section: Cell Viability Studymentioning
confidence: 56%
“…Besides, the biological effects of four Cu(II) complexes with Schiff base ligands on human colon carcinoma cells (HT-29) have been also investigated. All of them exhibited cytotoxic effects, with IC 50 values between 0.6 to 31 µM [50], and induced the mitochondria-dependent pathway of apoptosis [51]. Another Schiff base compound, Cu(BrHAP) 2 , demonstrated a potent anti-tumor effect in HT-29 cells (IC 50 = 2.87 ± 0.2) and induced elevation of reactive oxygen species (ROS) production and activation of caspases 3/7 and 9 [52].…”
Section: Cell Viability Studymentioning
confidence: 99%
“…drug development [40], catalysis [9], electronics and magnetism [41]. There have been several reports of monomeric and dimeric copper(II) complexes bearing this type of donor, acting as neutral, mono or dianionic ligands [6,8]. Therefore, it was decided to evaluate as a first approach the complexation potential of the synthesized molecules using Job's method.…”
Section: Complexation Studiesmentioning
confidence: 99%
“…NAHs are Schiff base-type compounds whose characteristic structural motif is the CH N NH C( O)-linkage. They are mainly synthesized by the condensation of a hydrazide and an aldehyde or ketone in the presence of a catalytic amount of glacial acetic acid [6]. Therefore, these types of compounds can act as effective O,N,O-chelating ligands when the corresponding aldehyde or ketone is o-hydroxy-substituted [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation